Overuse of antimicrobial prophylaxis in low-risk patients undergoing transurethral resection of the prostate (Swiss Medical Weekly, 2018)
OBJECTIVE To evaluate the current antimicrobial prophylaxis practices for low-risk patients undergoing transurethral resection of the prostate (TURP) or photoselective vaporisation of the prostate (PVP) in comparison with the antimicrobial prophylaxis recommendations of the European Association of Urology (EAU), which have been shown to effectively reduce infectious complications and antimicrobial resistance rates. METHODS In May 2017, we sent an anonymous online -survey to board-certified urologists in Germany, Austria and Switzerland, by use of the database directory of the respective urology associations. Besides demographical questions, urologists were asked about their sources of information on antimicrobial prophylaxis prescription and their prescribing patterns before, during and after surgery in patients without an indwelling catheter or significant bacteriuria undergoing TURP or PVP. RESULTS Overall, 374 of 5825 urologists responded, of whom 76% (286/374) performed TURP and 16% (60/374) PVP. For TURP and PVP, respectively: (i) 42% (119/286) and 33% (20/60) reported routine use of preoperative antimicrobial prophylaxis, which does not conform to guideline recommendations; (ii) 43% (124/286) and 52% (31/60) reported prescribing non-recommended perioperative antimicrobial prophylaxis regimens; and (iii) 60% (172/286) and 65% (39/60) routinely extended antimicrobial prophylaxis after surgery for up to one week. In summary, of the urologists who responded to the questionnaire, 74% (211/286) reported nonadherence to guidelines on antimicrobial prophylaxis for TURP. CONCLUSION A low adherence to guidelines for low-risk patients undergoing TURP or PVP was reported. Given these preliminary data, there is an urgent need to monitor adherence to antimicrobial prophylaxis guidelines in urology to reduce antimicrobial resistance rates.